Mass casualty incidents and B-Con training - Robaina, MD, Jose A.; Crawford, MD, Scott B.; Huerta, MPH, Diane; Austin, BA, Danielle; Wells, MD, Radosveta M.; Monks, PhD, Stormy M. (Journal of Emergency Management, 2018)
Objective: The purpose of this study was to determine if providing mass casualty training, utilizing the Bleeding Control for the Injured (B-Con) course would allow participants to feel more confident to provide bystander aid to wounded victims in a mass casualty incident (MCI). Design: Quasi-experimental pre-post intervention study. Setting: Participants were healthcare providers attending a trauma research conference hosted by a medical university. Interventions: Participants were given a group lecture in each of the three B-Con skill areas. These include: bleeding control with a tourniquet, bleeding control with gauze, and airway control with a jaw thrust. Participants were then divided into three groups and practiced each skill with instruction from B-Con certified trainers. Main outcomes measures: The primary outcome was scores from pre- to post-intervention in the categories of self-efficacy, perceived benefit, perceived susceptibility, perceived barriers, and perceived severity related to involvement in an MCI. Results: The study included 67 participants, all identifying as medical providers. Means in the categories of self-efficacy, perceived benefit, perceived susceptibility, perceived barriers, and perceived severity significantly increased from pre-intervention to postintervention among the paired variables. Conclusions: This study demonstrates the effectiveness of B-Con training in improving the confidence of participants. By increasing the number of persons who are trained for an MCI, there will be an increased probability that triage and immediate care will be rendered when needed. Future research needs to be completed evaluating the effect of training on a layperson study sample.